FROM THE VERGE OF BANKRUPTCY TO INDUSTRY LEADER USING BLUE OCEAN STRATEGY (BOS): THE CASE STUDY OF VINASOY (VIETNAM) - HUYNH, VAN THI CAM (2017)
This study examines the process of applying Blue Ocean Strategy as a turnaround strategy in public sector through a case study in Vietnam – Vinasoy. Overview about Blue Ocean Strategy and turnaround process have been introduced. Besides, characteristic of state firms in the world and in Vietnam in specific have been discussed through the document in the various deliberations. Besides, the role of leadership is mentioned in this research by using the concept of Blue Ocean Leadership. Using case study with historical approach combining with in-depth interview is the main research method. The call of further research on BOS as a turnaround strategy and state sector in different contexts with BOS has been emphasized.